Адміністративноправові засоби забезпечення законності в діяльності органів місцевого самоврядування - Ібрагімзаде, Е. Р. (КНУ ім. Т. Шевченка, 2023)
Дисертаційне дослідження спрямоване на розкриття адміністративноправових засобів забезпечення законності в діяльності органів місцевого самоврядування (ОМС) та окреслення можливих шляхів оптимізації їх правового регулювання. В роботі дістали подальшого розвитку теоретичні напрацювання щодо змісту законності в діяльності ОМС та удосконалено наукове розуміння особливостей і видів адміністративноправових засобів забезпечення законності в діяльності ОМС. За змістом законність в діяльності ОМС визначено як субрежим адміністративного права, в результаті чого доведено, що законодавчі положення, якими передбачається забезпечення законності в діяльності ОМС в Україні, потребують вдосконалення, оскільки неналежним чином врегульовують усі аспекти такого забезпечення, а в деяких випадках навіть спрямовані на централізацію публічної влади. Запропоновано внести зміни до чинного Закону № 280: визначити поняття «забезпечення законності в діяльності ОМС»; доповнити розділом «забезпечення законності в діяльності ОМС» (уточнити принципи, сутність, мету, завдання та засади внутрішнього організаційного контролю, громадського контролю, адміністративного нагляду і судового контролю за законністю діяльності ОМС; окреслити специфіку ЗЗ в діяльності органів і посадових осіб МС у період дії режимів воєнного та надзвичайного стану). Встановлено, що адміністративноправові засоби забезпечення законності в діяльності ОМС за змістом виступають гарантіями, серед особливостей визначено їх мету та завдання, коло адресатів, форми вираження. Систему основних видів досліджуваних засобів складають: (1) контроль: внутрішній, внутрішній організаційний, судовий; 2) адміністративний нагляд: загальний, спеціальний, особливий; 3) субсидіарна діяльність прокурора; 4) юридична відповідальність посадових осіб МС. Вперше розглянуто внутрішній контроль в ОМС з точки зору визначення його організаційної структури та форми діяльності суб’єктів, які його забезпечують. В результаті, виявлено цілий ряд проблем щодо повноважень окремих суб’єктів (дублювання, невизначеність; відсутність права звільняти чи виносити на розгляд пропозиції щодо звільнення порушників вимог законності), щодо правового регулювання процесу звітування перед громадою (практична відсутність положень, якими б були забезпечені чіткість, гласність та прозорість звітування), скасування актів ОМС. Запропоновано конкретні зміни до чинного законодавства щодо їх усунення. Окремо наголошено на необхідності розроблення Мін’юстом Рекомендації про врегулювання у Положенні про старосту порядку звітування старости. The dissertation thesis targets the disclosure of administrative and legal means of ensuring legality in the activities of local selfgovernment bodies (LSGB) and outlining possible ways to optimize their legal regulation. Theoretical provisions about the content of legality in the activities of LSGB are received further development in the thesis. Also, the scientific understanding of the features and types of administrative and legal means ensuring legality in the activities of LSGB is 7improved. The legality of the activities of LSGB is defined as a subregime of administrative law by its content, therefore it is proven that corresponding legislative provisions need to be improved because they do regulate not enough all aspects of this ensuring and moreover in some cases are even aimed at the centralization of public power. The amend the current Law 280 is suggested: to define a definition of “ensuring of legality in the activities of LSGB”; to supplement the Chapter “The ensuring of legality in the activities of LSGB” (to clarify the principles, the essence, purpose, tasks, and fundamentals of internal organizational control, public control, administrative supervision, the control by the court on legality in activities of LSGB; defining specific of ensuring of legality these activities during the period of military regimes and emergency regimes in the country). It has been established that administrative and legal means of ensuring legality in the activities of LSGB by their content are the guarantees which have features in their purpose and tasks, subjects of addressing, and forms of expression. The system of the main types of researched means is composed: 1) control: internal, internal organizational, judicial by the court; 2) administrative supervision: general, special, specific; 3) subsidiary activities of the prosecutor; 4) legal liability of officials of the local selfgovernment. For the first time, internal control in the local government was considered from the point of view of determining its organizational structure and the form of activity of the entities that provide it. As a result, a number of problems were identified regarding the powers of individual subjects (duplication, uncertainty; lack of the right to dismiss or submit for consideration a proposal for the dismissal of violators of the requirements of legality), regarding the legal regulation of the process of reporting to the community (the practical absence of provisions that would ensure clarity, publicity, and transparency of reporting), cancellation of local government acts. Specific changes to the current legislation regarding their elimination are proposed. The need for the Ministry of Justice to develop a Recommendation on the regulation of the reporting procedure of the headman in the Regulations on the headman was separately emphasized. Also for the first time, as a result of the analysis of scientific provisions regarding the essence of administrative supervision in the activities of local government organizations, it has been proven that the modern model of administrative supervision over the activities of local government organizations in Ukraine is aimed at the centralization of public power, which is carried out by the National Security and Defense Council of Ukraine and tempor ary state bodies (ACA and military administrations). The expediency of the legislative clarification of subjects and objects of control and the procedure for control over the performance of delegated powers by local government organizations and their offic ials has been substantiated (to supplement Law No. 586); clarifying the possibility of the Military Civil Administration to apply to the court with a claim to declare an act of local government, their officials, as illegal, if such acts threaten the safety and normalization of the life of the population in the area of repelling armed aggression of the Russian Federation (amend Law No. 141 in corresponding part); establishment of the right of the military administration to apply to the court with a claim to declare illegal acts of the local government, their officials, if they make it impossible to properly ensure defense, public safety and order in the relevant territory (amend Law No. 389 in corresponding part).
The administrative and legal means of ensuring legality in the activities of local selfgovernment bodies
Keywords: місцеве самоврядування; законність; адміністративно-правові засоби; нагляд; відповідальність; публічний інтерес; адміністративні процедури; публічна адміністрація; адміністративне оскарження; законодавче регулювання; local selfgovernment; legality; administrative and legal means; supervision; liability; public interest; administrative procedure; public administration; administrative appeal; legislative regulation